2020
DOI: 10.1177/2051415820956431
|View full text |Cite
|
Sign up to set email alerts
|

Retroperitoneoscopic nephrectomy: current status

Abstract: The classic retroperitoneal open surgical access to the kidney has been duplicated while performing laparoscopy but is less common than transperitoneal laparoscopy. We reviewed minimally invasive retroperitoneoscopic nephrectomy as a part of the international consultation on urological diseases and European Association of Urology international consultation on minimally invasive surgery in urology. A Pubmed/Medline search was performed to identify studies assessing the feasibility, safety and efficacy of laparo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 43 publications
1
4
1
Order By: Relevance
“…Moreover, there were no significant differences in postoperative renal function and haemoglobin drop between the two donor groups. This finding is consistent with previous literature reports on the safety of the new technique of RALDN 8,9,17–19 . Moreover, the studies suggested that robotic surgery has some advantages compared with laparoscopic surgery regarding surgical ease in renal hilar dissection and reduction of donor morbidity 20,21 …”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Moreover, there were no significant differences in postoperative renal function and haemoglobin drop between the two donor groups. This finding is consistent with previous literature reports on the safety of the new technique of RALDN 8,9,17–19 . Moreover, the studies suggested that robotic surgery has some advantages compared with laparoscopic surgery regarding surgical ease in renal hilar dissection and reduction of donor morbidity 20,21 …”
Section: Discussionsupporting
confidence: 91%
“…Previous studies showed an equal or a shorter mean hospital stay in the RALDN group. 5,17,22,26 In our study, there were no significant differences in serum creatinine at 1 month after transplantation between the two groups of respective recipients. There were no cases of slow graft function and delayed graft function during the follow-up interval.…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations